2009
DOI: 10.1021/la9001169
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pluronic F-127 on Surfaces with Different Hydrophobicities Probed by Quartz Crystal Microbalance with Dissipation

Abstract: Triblock copolymers of polyethylene oxide (PEO) and polypropylene oxide (PPO), that is, PEOn-PPOm-PEOn, better known as Pluronic can adsorb to surfaces in either a pancake or a brushlike configuration. The brushlike configuration is advantageous in numerous applications, since it constitutes a surface repellent to proteins and microorganisms. The conformation of the adsorbed Pluronic layer depends on the hydrophobicity of the substratum surface, but the hydrophobicity threshold above which a brushlike conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 22 publications
(28 reference statements)
6
101
0
Order By: Relevance
“…2b give additional information on the existence of rearrangement of the preadsorbed chains, which is related to the type of behaviour of the plot (linear or non-linear trends). 27 Fig. 2b also allows obtaining qualitative information on energy/entropy balance in the adsorption process.…”
Section: Adsorption Processmentioning
confidence: 99%
“…2b give additional information on the existence of rearrangement of the preadsorbed chains, which is related to the type of behaviour of the plot (linear or non-linear trends). 27 Fig. 2b also allows obtaining qualitative information on energy/entropy balance in the adsorption process.…”
Section: Adsorption Processmentioning
confidence: 99%
“…Conversely, in the zones outside of the trench, which were protected from plasma oxidation by the PDMS slab, we expected Pluronic F127, a triblock copolymer consisting of a central hydrophobic poly(propylene oxide) (PPO) block, flanked by two blocks of poly(ethylene oxide) (PEO), to adsorb to the untreated hydrophobic PDMS substrate and repel cell attachment. 58,59 Pluronic forms a "brushlike" molecular conformation, in which the hydrophobic PPO blocks adsorb to the hydrophobic PDMS substrate and the hydrophilic PEO blocks face the solution, resisting protein adsorption by repulsive osmotic force, thereby minimizing cell adhesion. 59,60 We found that our micropatterning scheme supported long-term micropatterned cultures of myotubes within trenches ( Figure 6).…”
Section: Micropatterning Of Myoblasts and Myotubes In Trenchesmentioning
confidence: 99%
“…As more and more sites were occupied, the changes in frequency shift related to adsorption slowed down, and a plateau was reached. At this stage, it is assumed that Plu forms a brush structure with relatively high density on Ti/OPA and SS/OPA, which prevents further Plu molecules to approach (Nejadnik et al 2009). It has been reported (Nejadnik et al 2009) that PEO-PPO-PEO can form a brush structure on hydrophobic surfaces with WCA above 80°, which is then effective to reduce protein adsorption (Schroen et al 1995).…”
Section: Competitive Plu and Protein Adsorption Examined By Xps And Tmentioning
confidence: 99%
“…At this stage, it is assumed that Plu forms a brush structure with relatively high density on Ti/OPA and SS/OPA, which prevents further Plu molecules to approach (Nejadnik et al 2009). It has been reported (Nejadnik et al 2009) that PEO-PPO-PEO can form a brush structure on hydrophobic surfaces with WCA above 80°, which is then effective to reduce protein adsorption (Schroen et al 1995). In contrast, PEO-PPO-PEO can form a pancake structure on hydrophilic surfaces (Schroen et al 1995), which is insufficient 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Chang et al 2010).…”
Section: Competitive Plu and Protein Adsorption Examined By Xps And Tmentioning
confidence: 99%
See 1 more Smart Citation